Formação de professores de geografia no brasil, Na espanha e em portugal: uma leitura das estruturas curriculares vigentes em 2013 - Shimizu, Rita De Cassia Gromoni; Pezzato, João Pedro (Faculdade de Educação da Universidade Federal de Minas Gerais, 2017)
Abstract: This paper aims to discuss the curriculum frameworks of 10 Geography teacher graduation courses and concern institutions of three nationalities, in other words, one institution per Brazilian region, one institution from the Galicia region (Spain), and one institution from the Minho region (Portugal). It concerns a qualitative survey, based on documental analysis (obtained in 2013), and in the theoretical references in the fields of curriculum studies and teacher education. The qualitative methodology, with content analysis, was the methodological option. Despite the relevance pointed in the theoretical contributions of the teacher education field in Brazil, as well as in Spain and Portugal, the interdisciplinary attempts, articulation of theory and practice, interaction between university and internship field, insertion of the survey and technologies towards teaching, in the initial academic teaching education, presented themselves in a precise manner, not permeating all the analyzed documents.

Resumo: Este artigo tem como objetivo discutir as estruturas curriculares de 10 cursos de formação de professores de Geografia em instituições de três nacionalidades: cinco brasileiras, uma por região - sendo que uma delas teve dois campi analisados -; uma da região da Galícia (Espanha); e uma da região do Minho (Portugal). Trata-se de pesquisa de cunho qualitativo, baseada em análise documental (obtida em 2013) e em referenciais teóricos do campo dos estudos curriculares e da formação de professores. O estudo baseou-se na metodologia qualitativa, com análise de conteúdo. A despeito da relevância apontada nas contribuições teóricas do campo da formação de professores, tanto no Brasil, como na Espanha e em Portugal, as iniciativas de interdisciplinaridade, articulação teoria-prática, interação entre a universidade e o campo de estágio, inserção da pesquisa e de tecnologias voltadas ao ensino na formação inicial para a docência apresentaram-se de maneira pontual, não permeando todos os documentos analisados.
Geography teacher education in brazil, spain and potugal: readout of the curriculum frameworks prevailed in 2013
Keywords: Curriculum; Geography; Teacher education.; Currículo; Formação de professores; Geografia.